Analisis Sekuen Probe Gena Shiga Like Toxin-2 dari Isolat Lokal Escherichia coli O157:H7 (PROBE SEQUANCE ANALYSIS OF SHIGA LIKE TOXIN-2 GEN FROM ESCHERICHIA COLI O157:H7 LOCAL ISOLATES) - Suardana, I Wayan; Sujaya, I Nengah; Artama, Wayan Tunas (Jurnal Veteriner, 2013)
A Shiga-like toxin producing Escherichia coli O157:H7 was detected in faecal samples of cattle, andhuman as well as in beef. The performance of agent indicated that it has been identified as harmful andoften life-threatening zoonotic agent. It is therefore important to analysed the genetic characteristic ofShiga toxin Escherichia coli (STEC) and to develop a diagnostic probe in order  to optimalized of diagnostictest  for the agent. The  study was started by amplifiying  stx2 gene, purifying of PCR product, sequencingof stx2 gene, analyzing  of phylogenetic tree, and finally  by analyzing   of  diagnostic  probe candidate.Homology study showed that the genetic sequence of the local isolate of  E. coli O157:H7 i.e SM25(1)isolated from cattle feces has  a genetic and fuctional similarity with  the control isolate i.e E. coli O157:H7ATCC 43894 originated from human.  Further study showed that a probe with  foreward primer  sequanceof 5’-AATTTATATGTGGCCGGGTTC-‘3 which were respectively designed as a PFS and PRS 176 bp product.Appeared to be potential candidate of diagnostic probe for the agent.
Keywords: E.coli O157:H7, molecular biology, probe, stx2 gene